Hubungan Tingkat Pengetahuan Ibu Dan Dukungan Suami Dengan Pemilihan KB Implan Di Puskesmas Sudiang Raya Kota Makassar - Nuralviani Nuralviani; Sri Wahyuni; Uswatun Kasanah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Knowledge of couples of childbearing age about Implanable contraception is one factor in choosing the use of Implanable contraceptives. The better a person's knowledge of contraceptives, the more rational they are in using contraceptives. Support from the husband in the use of contraception is very necessary. Married couples must jointly choose the best contraceptive method, cooperate with each other in use, finance contraceptive expenditure and pay attention to red flags. (Laras T.N, 2018). This study aims to analyze the relationship between the level of knowledge of mothers and husband support with the selection of Implanable birth control at the Sudiang Raya Health Center in Makassar City. The type of research conducted uses descriptive analytics with a Cross Sectional Study approach. The research will be conducted in April - May 2023 at the Sudiang Raya Health Center in Makassar City. The sample size used in this study was 38 respondents. It can be concluded that from the results of statistical tests show that there is a relationship between the level of knowledge and the selection of Implan birth control with a value of p = 0.004. The results showed that there was a relationship between husband support and the selection of Implan birth control with a value of p = 0.018. The Health Office and midwives, especially those in charge of the poly family planning section, should always socialize about contraceptives and the advantages and disadvantages of contraceptives so that people can easily choose contraceptives that are in accordance with their wishes.